Analysis of the Participation of Reproductive Age Couples in the Family Planning Program in South Sulawesi Province - Sri Budiarti Ariny; Rabina Yunus; M. Ramli AT (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The purpose of this research is to analyze the factors related to the participation of couples of childbearing age in the family planning program in South Sulawesi Province. This research is quantitative descriptive research using secondary data from the March 2020 National Socioeconomic Survey (NSS) compiled and obtained from the Central Statistics Agency (CSA) of South Sulawesi Province. The results showed that 48.2 percent of the 9,741 or equivalently 4,697 married women aged 15–49 years who participated in the family planning program had elementary school education or less, were aged 25–34 years, had an age of first marriage under 19 years, had an activity status of not working, lived with their husbands, and lived in a rural area. It is hoped that policymakers should increase socialization and counseling on family planning programs and contraceptive methods in urban areas and among women with high school education and above because women in this category have indications of low participation in family planning programs in South Sulawesi Province.